Mixed application of raw amino acid powder and Trichoderma harzianum fertilizer for the prevention and management of apple replant disease - Weixiao Tang; Yi Lü; Rong Zhang; Xin Wang; Haiyan Wang; Mei Wang; Xuesen Chen; Xiang Shen; Chengmiao Yin; Zhiquan Mao (Journal of Integrative Agriculture, 2025)
Apple replant disease (ARD) is mainly caused by biological factors, and it severely restricts the development of the apple industry. The use of biological control measures to alleviate ARD is critically important for the sustainable development of the apple industry. The effects of raw amino acid powder and Trichoderma harzianum fertilizer on plant biomass, leaf and root indexes, soil physical and chemical properties, soil enzyme activities, and the soil fungal community were studied under pot and field conditions using Malus hupehensis Rehd. seedlings and grafted trees (Fuji New 2001/M9T337) as experimental materials. We found that the application of the materials significantly promoted plant growth, increased the leaf photosynthesis and chlorophyll content, root respiration rate, root antioxidant enzyme activities, and soil enzyme activities, significantly reduced the number of Fusarium sp. in soil, and significantly increased the abundance of beneficial fungi. In conclusion, the mixed application of raw amino acid powder and T. harzianum fertilizer is an effective method for the prevention and management of ARD.